Horizontal Spatial Metaphor Representation of Social Status in Chinese Culture - Sun, Hongri; Liu, Danfeng (Frontiers in Psychology, 2021)
The mapping relationship between social status and horizontal space (left/right) in Chinese culture has a long history. In order to explore what representation pattern of horizontal spatial metaphor of social status is in Chinese culture, this study introduced two direct measurements, implicit relational assessment procedure (IRAP) paradigm and spatial placement task to evaluate the mapping of social status to horizontal space. A total of 144 Chinese undergraduates participated in the research wherein they were asked to place certain words indicating social status in either left or right boxes before or after IRAP computer test. The results from the two measurements consistently showed that the mode of HIGH SOCIAL STATUS-LEFT and LOW SOCIAL STATUS-RIGHT(HLLR) had advantage over of HIGH SOCIAL STATUS-RIGHT and LOW SOCIAL STATUS-LEFT(HRLL), implying that the representation pattern of horizontal spatial metaphor of social status for Chinese is HIGH SOCIAL STATUS-LEFT and LOW SOCIAL STATUS-RIGHT. However, the result convergence of the two measurements was not high which suggests that embodiment effect has multiple characteristics and new specific experimental paradigms should be created to measure it.